Development of Student Worksheets Based on a Multi-Representation Approach to Improve Students' Mastery of Sound Wave Concepts - Aris Doyan; Muhammad Matori Rahman; Sutrio Sutrio (Postgraduate, University of Mataram, 2021)
This development research aims to produce a product in the form of student worksheets based on a multi-representation approach to improve students' mastery of the sound wave concept that is valid, and effective. The product developed is student worksheets. The research design used is a 4D model consisting of Define, Design, Develop and Disseminate. Data collection techniques used validation sheets and concept mastery evaluation tools. Device validity data were analyzed using a Likert scale. Product effectiveness data were analyzed using Gain standards. Product validity was assessed by three expert validators and three practitioner validators. The assessment by the expert validator is 3.50 and by the practitioner validator it is 3.70 with valid criteria. The average result of the N Gain test for mastery of Sound Wave concepts is 0.73 in the high category. So, it can be concluded that student worksheets based on a multi-representation approach to improve students' mastery of sound wave concepts are valid and effective